A review on recovery of extracellular biopolymers from flocculent and granular activated sludges: Cognition, key influencing factors, applications, and challenges. (November 2022) - Chen, Xingyu; Lee, Yu-Jen; Yuan, Tian; Lei, Zhongfang; Adachi, Yasuhisa; Zhang, Zhenya; Lin, Yuemei; van Loosdrecht, Mark C.M.
Graphical abstract: Highlights: Excess sludge can be turned into wealth by producing EPS-based biomaterials. Recovery of extracellular biopolymers from AS, BAGS, and A-BAGS is reviewed. Existing ALE extraction and identification methods are updated but with limitations. Combining the properties and functions of biopolymers benefits further applications. Future perspectives of sludge-based extracellular biopolymers recovery are outlined. Abstract: A reasonable recovery of excess sludge may shift the waste into wealth. Recently an increasing attention has been paid to the recycling of extracellular biopolymers from conventional and advanced biological wastewater treatment systems such as flocculent activated sludge (AS), bacterial aerobic granular sludge (AGS), and algal-bacterial AGS processes. This review provides the first overview of current research developments and future directions in the recovery and utilization of high value-added biopolymers from the three types of sludge. It details the discussion on the recent evolvement of cognition or updated knowledge on functional extracellular biopolymers, as well as a comprehensive summary of the operating conditions and wastewater parameters influencing the yield, quality, and functionality of alginate-like exopolymer (ALE). In addition, recent attempts for potential practical applications of extracellular biopolymers are discussed, suggesting research priorities for overcoming identification challenges and future prospects.